2016
DOI: 10.1097/mao.0000000000001211
|View full text |Cite
|
Sign up to set email alerts
|

The Enigma of Poor Performance by Adults With Cochlear Implants

Abstract: Objective Considerable unexplained variability and large individual differences exist in speech recognition outcomes for postlingually deaf adults who use cochlear implants (CIs), and a sizeable fraction of CI users can be considered “poor performers.” This paper summarizes our current knowledge of poor CI performance, and provides suggestions to clinicians managing these patients. Method Studies are reviewed pertaining to speech recognition variability in adults with hearing loss. Findings are augmented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
128
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(142 citation statements)
references
References 89 publications
(77 reference statements)
0
128
1
13
Order By: Relevance
“…Some specific neurocognitive skills, such as working memory capacity, appear to be more strongly related to speech perception and recognition and may be more strongly related than more general cognitive abilities, such as nonverbal intelligence (for a review, see Akeroyd) 1 . Working memory (Lyxell et al; 29 Tao et al) 52 as well as inhibitory control (Moberly et al 31 ), verbal learning and memory (Pisoni et al) 25 , and processing speed (Tinnemore et al) 53 have been linked to individual differences in speech recognition among adult CI users. In addition, although a strong relation has not been established, nonverbal reasoning skills have recently been found to be associated with individual performance among postlingually deafened adult CI users, independently of age (Mattingly et al) 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Some specific neurocognitive skills, such as working memory capacity, appear to be more strongly related to speech perception and recognition and may be more strongly related than more general cognitive abilities, such as nonverbal intelligence (for a review, see Akeroyd) 1 . Working memory (Lyxell et al; 29 Tao et al) 52 as well as inhibitory control (Moberly et al 31 ), verbal learning and memory (Pisoni et al) 25 , and processing speed (Tinnemore et al) 53 have been linked to individual differences in speech recognition among adult CI users. In addition, although a strong relation has not been established, nonverbal reasoning skills have recently been found to be associated with individual performance among postlingually deafened adult CI users, independently of age (Mattingly et al) 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the source of the variability in CI performance is still unknown. In general, factors explaining this variation in individual speech perception ability include the bottom-up processing of the auditory periphery to acoustic features (including spectral and temporal information) and topdown cognitive processing at the cortex level (Moberly et al, 2016). However, demographic factors such as age at implantation and duration of deafness merely explain 20% of the variability in CI outcomes (Lazard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For adults who are postlingually deafened, factors that contribute to CI outcome include the amount of residual hearing, duration of deafness, neurocognitive functioning, device implanted, method of implantation, surgeon experience, postoperative complications and environmental variables such as socioeconomic status (Moberly et al, 2016). However, two recent studies on a cohort of 2,251 patients conducted using two different statistical modeling methods found that only 10.5% and 22% of variance in postoperative speech perception testing could be accounted for by considering up to 9 different clinical factors (Blamey et al, 2013; Lazard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%